1969
DOI: 10.2466/pr0.1969.24.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Parental Antecedents of Internal-External Control of Reinforcement

Abstract: Two exploratory studies were conducted involving children's reports of parental behavior and parents' child-rearing and internal-external control (I-E) attitudes as antecedents of children's beliefs that the reinforcements they receive are a consequence of their own behavior (internals). Internals, as contrasted to those who believe that reinforcements tend to occur independently of their behavior (externals), reported their parents as showing less rejection, hostile control, and withdrawal of relations, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 12 publications
4
28
0
Order By: Relevance
“…Students with an internal locus of control reported their parents to be more positive and lower in rejection, control, inconsistent discipline, and love withdrawal as compared to those with an external locus of control. Davis and Phares (1969) suggested that children might develop an external locus of control in order to avoid the anxiety associated with the increased rejection and hostility. Instead of accepting the failure or deprecation this may cause, they attribute aversive events as outside of their control.…”
Section: Empirical Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Students with an internal locus of control reported their parents to be more positive and lower in rejection, control, inconsistent discipline, and love withdrawal as compared to those with an external locus of control. Davis and Phares (1969) suggested that children might develop an external locus of control in order to avoid the anxiety associated with the increased rejection and hostility. Instead of accepting the failure or deprecation this may cause, they attribute aversive events as outside of their control.…”
Section: Empirical Studiesmentioning
confidence: 98%
“…Thus, researchers have investigated the role it plays in the development of anxiety. The rationale behind these studies is that overcontrolling parental behavior leads children to believe that events are outside of their control (Davis and Phares, 1969). In order to properly present theoretical models in this area, it is first necessary to establish that there is a difference in the family environments of children with different perceptions of control.…”
Section: Current Conceptual Models Related To Anxiety Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly it would be expected that unpredictable parents would encourage the development of attitudes of External control (p.24). Davis and Phares (1969) and MacDonald (1971) Within this framework, three aspects of the definitional process seemed particularly relevant; namely, the inmates' definitions of the institution (1) as an opportunity structure, (2) as an authority structure and (3) as a predictable environment where future events are contingent on one's behavior (pp.795-796).…”
Section: Figuresmentioning
confidence: 99%